Polymorphisms and colorectal tumor risk. - Houlston, R; Tomlinson, I (2001)
BACKGROUND and AIMS: Increasingly, studies of the relationship between common genetic variants and colorectal tumor risk are being proposed. To assess the evidence that any of these confers a risk, a systematic review and meta-analysis of published studies was undertaken. METHODS: Fifty studies of the effect of common alleles of 13 genes on risk were identified. To clarify the impact of individual polymorphisms on risk, pooled analyses were performed. RESULTS: Of the 50 studies identified, significant associations were seen in 16, but only 3 were reported in more than one study. Pooling studies, significant associations were only seen for 3 of the polymorphisms: adenomatosis polyposis coli (APC)-I1307K (odds ratio [OR] = 1.58, 95% confidence interval [CI]: 1.21-2.07); Harvey ras-1 variable number tandem repeat polymorphism (HRAS1-VNTR; OR = 2.50, 95% CI: 1.54-4.05); and methylenetetrahydrofolate reductase (MTHFR)(Val/Val) (OR = 0.76, 95% CI: 0.62-0.92). For tumor protein 53 (TP53), N-acetyl transferase 1 (NAT1), NAT2, glutathione-S transferase Mu (GSTM1), glutathione-S transferase Theta (GSTT1), and glutathione-S transferase Pi (GSTP1) polymorphisms, the best estimates are sufficient to exclude a 1.7-fold increase in risk of colorectal cancer. CONCLUSIONS: APC-I1307K, HRAS1-VNTR, and MTHFR variants represent the strongest candidates for low penetrance susceptibility alleles identified to date. Although their genotypic risks are modest, their high frequency in the population implies that they may well have considerable impact on colorectal cancer incidence. Determining precise risk estimates associated with other variants and gene-gene and gene-environment interactions will be contingent on further studies with sample sizes larger than typically used to date.